1984
DOI: 10.1111/j.1471-4159.1984.tb00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Phospholipid Content and Na+, K+‐ATPase Activity During Ischemia and Postischemic Reperfusion in the Mongolian Gerbil

Abstract: Using bilateral carotid artery occlusion in adult gerbils we examined the effects of ischemia and ischemia/reperfusion on cerebral phospholipid content and Na+,K+-ATPase (EC 3.6.1.3) activity. In contrast to the large changes in phospholipid content and membrane-bound enzyme activity that have been observed in liver and heart tissues, we observed relatively small changes in the cerebral content of total phospholipid, phosphatidylcholine (PC), phosphatidylserine (PS), and phosphatidylethanolamine (PE) following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…According to mechanisms related to de layed neuronal death, intracellular calcium overload (24), the release of excitotoxin (25), accumulation of free fatty acid (26), alter nations of protein synthesis (27) and so on may be involved. The delayed neuronal death inhibition seen with minaprine remains the subject of ongoing studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to mechanisms related to de layed neuronal death, intracellular calcium overload (24), the release of excitotoxin (25), accumulation of free fatty acid (26), alter nations of protein synthesis (27) and so on may be involved. The delayed neuronal death inhibition seen with minaprine remains the subject of ongoing studies.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshida et al 10 observed a 4% decrease in PC (not significant) and a 16% decrease in PE content of gerbil brain after 30 minutes of ischemia. Enseleit et al 5 reported small changes in the total cerebral phospholipid, PC, phosphatidylserine (PS), and PE content, which might depend on the different rates of lipid metabolism of gerbil brains subjected to various periods of ischemia. These discrepancies are probably due to a combination of factors such as differences in sampling procedures, analytic methodology, animal model, and duration of the ischemic insult.…”
Section: Changes In Phospholipid Molecular Species During Ischemiamentioning
confidence: 99%
“…26 " 28 Ganglioside protection from loss of Na, K-ATPase activity may indicate protection of membrane structure and function since there is considerable evidence that ischemia causes significant reductions in this enzyme's activity. 31 By stabilizing membrane function and therefore "normal" ionic gradients, membrane failure and subsequent deterioration may well be minimized. The protection of this enzyme from the loss of activity probably reflects effects on one or a series of biochemical changes (e.g., lipid hydrolysis, phospholipase activation, production and membrane action of arachidonic acid, ionic imbalance) that occur as a result of injury and lead to membrane failure.…”
Section: Resultsmentioning
confidence: 99%